Insertion of a repetitive element at the same position in the 5'-flanking regions of two dissimilar yeast tRNA genes. - Sandmeyer, S B (1982)
The regions 5' proximal to many yeast tRNA genes exhibit a high frequency of DNA sequence polymorphisms. DNA sequence analysis of polymorphic variants of SUQ5, a tRNA Ser UCA gene, and SUP2, a tRNA Tyr gene, shows that in each case one sequence variant of the tRNA gene is 346 base pairs longer than the other. The longer variants appear to have arisen from the shorter ones by the insertion of nearly identical copies of a 341-base pair sigma element into a site 16 base pairs upstream from the 5' ends of the tRNA-coding regions. The sequences of the two copies of the sigma element differ at only five positions. The element has a number of properties that are typical of many transposable elements: (i) there is a perfect eight-base-pair inverted repeat at its ends, (ii) these ends are flanked by a five-base-pair direct repeat of a sequence that occurs only once in the target DNA, (iii) there are approximately 20 copies of the element in the yeast genome, and (iv) there is considerable strain-to-strain variation in the sizes of the restriction fragments on which these copies lie. The presence of the sigma element has no gross effect on the phenotype of a SUP2 ochre suppressor. Analysis of the SUQ5 and SUP2 sequences favors the hypothesis that sigma is a transposable element with a novel type of insertion specificity, which is primarily based on the presence of a tRNA-coding region a fixed distance from the insertion site, rather than on the immediate target sequences.